2018
DOI: 10.1016/j.labeco.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Education outcomes and the labor market

Abstract: The quality of education appears to be negatively correlated with both the overeducation of workers at the tasks they perform and the unemployment rate across EU-15 countries, and positively correlated with the wage premium associated to tertiary education. We develop a model of the labor market with frictions to quantitatively investigate the impact of the education outcomes on the labor market. We show that both the ability of educated and non educated workers have sizable effects on the incentives of firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…The negative effect of being over-educated in the labor market declines with years of experience. Similarly [ 35 ], also found a negative correlation between education quality and over-education in the EU-15. In another recent study [ 36 ] found evidence of a significant incidence of over-education in Bosnia-Herzegovina and low return to over-education compared to those with the matched level of education.…”
Section: Literature Reviewmentioning
confidence: 72%
“…The negative effect of being over-educated in the labor market declines with years of experience. Similarly [ 35 ], also found a negative correlation between education quality and over-education in the EU-15. In another recent study [ 36 ] found evidence of a significant incidence of over-education in Bosnia-Herzegovina and low return to over-education compared to those with the matched level of education.…”
Section: Literature Reviewmentioning
confidence: 72%
“…Overeducation is rather a product of their lower skills and/or frustration with their mismatch that makes them do less childcare time. The former is consistent with the results found in the overeducation literature that overeducated individuals have lower skills (Tsai, 2010; Obiols-Homs and Sánchez-Marcos, 2018). Our results complement the well-established findings that highly educated parents devote more time to childcare.…”
Section: Discussionmentioning
confidence: 99%
“…Pendidikan akan menjadi sinyal yang efisien jika ,model marjin diasumsikan sebagai opportunity cost tenaga kerja lebih dari nol. Utilitas pekerja ditunjukan kedalam fungsi U(R,s,d,h) = R+d-(s/h), dimana R merupakan pendapatan, sama dengan upak jika individu dipekerjakan dan bukan 0, d merupakan indikator fungsi 0 jika bekerja dan 1 jika tidak bekerja, dan sinyal adalah s sebagai tingkat pendidikan (Obiols-Homs & Sánchez-Marcos, 2018).…”
Section: Efisiensi Pendidikan Sebagai Alat Sinyalunclassified